QUALITY OF NURSING CARE AND DETERMINANTS OF PATIENTS’ SATISFACTION IN PUNJAB INSTITUTE OF CARDIOLOGY IN LAHORE, PAKISTAN (The Research of Medical Science Review, 2025)
Background: Patient satisfaction with nursing care is a vital indicator of overall satisfaction with hospital services and a reflection of the quality of healthcare delivery. Despite its importance, the level of satisfaction with nursing care in teaching hospital in Lahore, Pakistan, remains underexplored.Aim: This study aimed to evaluate the level of patient satisfaction with the quality of nursing care in surgical wards of Punjab Institute of Cardiology in Lahore.Methods: The study was conducted in selected Punjab Institute of Cardiology (PIC) in Lahore from June to December 2024. A structured and culturally adapted version of the Patient Satisfaction with Nursing Care Quality Questionnaire (PSNCQQ), originally developed by Dr. Laschinger, was used for data collection. The study included patients who had undergone various surgical procedures, excluding those with post-operative wound infections. The tool assessed nine key dimensions of nursing care.Results: A total of 178 out of 180 surgical inpatients were successfully interviewed through structured questionnaires. In cases involving language or literacy barriers, attendants assisted in communication. Findings indicated that although many patients expressed overall satisfaction, several areas—particularly privacy and maintaining a restful environment—fell short of patient expectations. These gaps highlight the need for focused improvements in interpersonal and environmental aspects of care.Conclusion: Nursing care plays a fundamental role in shaping the patient experience throughout the hospital stay. Strengthening nurse-patient communication and reinforcing patient dignity and comfort are essential to improving satisfaction levels in teaching hospitals of Lahore.